PENYULUHAN TENTANG KUALITAS LAYANAN FARMASI DI RUMAH SAKIT GRANMED LUBUK PAKAM - Nerdy Nerdy; Nurul Aini Siagian; Saiful Batubara; Silmi Hayati (INSTITUT KESEHATAN DELI HUSADA, 2021)
The hospital is one of the health facilities where health efforts are carried out. Health efforts are every activity to maintain and improve health, aiming to realize optimal health degrees for the community. Pharmaceutical services as one element of the main services in hospitals, are an inseparable part of the service system in hospitals that are oriented to patient care, providing quality drugs, including affordable clinical pharmacy services for all levels of society. The practice of pharmacy services is an integrated activity, with the aim of identifying, preventing and solving problems related to drugs and health. Hospital pharmacy services are one of the activities in hospitals that support quality health services. This is explained in the Decree of the Minister of Health Number 1333/Menkes/SK/XII/1999 concerning Hospital Service Standards, which states that hospital pharmacy services are an inseparable part of the hospital health service system that is oriented to patient care, drug provision. quality, including clinical pharmacy services, which are affordable for all levels of society. Currently, pharmacists who work at the Granmed Lubuk Pakam Hospital are required to be able to provide patient-oriented clinical pharmacy services. The aim is to improve patient safety. Pharmacists are required to play a role in improving patient safety, especially for drug-related problems.